2019
DOI: 10.1002/ldr.3275
|View full text |Cite
|
Sign up to set email alerts
|

Changes in rhizosphere bacterial and fungal community composition with vegetation restoration in planted forests

Abstract: Soil microbial communities affect nutrient cycling and ecosystem functioning. However, the variations in microbial diversity and community composition within degraded landscapes remain unclear. Using high-throughput sequencing of bacterial 16S ribosomal RNA genes and internal transcribed spacer fungal sequences, we investigated the rhizosphere microbial diversity and community of coniferous Pinus tabulaeformis Carr. forests in degraded lands across a chronosequence that spanned over 60 years (10, 25, 40, and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 69 publications
(85 reference statements)
10
36
0
Order By: Relevance
“…Different letters over the box-and-whisker figures indicate significant differences highest in areas that had been selectively logged three times (Figure 4). Previous study confirmed that the surrounding local properties influenced the distribution and relative abundance of most fungi (Liu, Chen et al, 2019). In our study, soil properties exhibited considerable variation among the selective logging intensities (Table 1), which suggests that various soil properties can affect the composition of fungal communities.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Different letters over the box-and-whisker figures indicate significant differences highest in areas that had been selectively logged three times (Figure 4). Previous study confirmed that the surrounding local properties influenced the distribution and relative abundance of most fungi (Liu, Chen et al, 2019). In our study, soil properties exhibited considerable variation among the selective logging intensities (Table 1), which suggests that various soil properties can affect the composition of fungal communities.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the intensity of selective logging affected the composition of fungal communities by affecting AP, which is in contrast to other types of the soil microbial community. Although AP is usually limited in soil, microbial communities can transform the soil nutrient elements and increase availability (Liu, Chen, et al, 2019). We also observed a significant correlation between AP and the composition of fungal communities, indicating that AP is an important determinant.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As the main decomposer of organic matter (cellulose, lignin, and pectin) in soil, Ascomycota had the ability of degrading rotten organic substrates (Yelle et al 2008). Basidiomycota, which was typically saprotrophic (Guo et al 2018), like Ascomycota, was characterized with environment-loving and the decomposition of organic matter (Liu et al 2019), and played a vital role in degrading litters especially with high lignin content in soil (Ye et al 2020). Furthermore, previous studies had shown that there might be a competitive relationship between the microbial groups of Ascomycota and Basidiomycota, resulting in a negative correlation between the relative abundances of the two phyla (Ye et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the physical and chemical properties of soils change considerably with depth (de Araujo Pereira et al, ). Nutrients are typically more concentrated in the topsoil than in the subsoil, mainly due to plant root exudates, root detritus, plant litter, and animal activities (Eldridge, Delgado‐Baquerizo, Woodhouse, & Neilan, ; Liu et al, ). Generally, subsoil exhibits a firmer, finer texture, with much lower organic matter content than topsoil.…”
Section: Introductionmentioning
confidence: 99%